2020
DOI: 10.1177/1179173x20949270
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Level Factors Associated with Oncology Provider-Delivered Brief Tobacco Treatment Among Recently Diagnosed Cancer Patients

Abstract: Background: A cancer diagnosis is seen as a “teachable moment” for patients to consider changing their behavioral risk factors, such as smoking. It also offers an opportunity for oncology providers to engage in a dialogue about how they can support patients changing their smoking behaviors. Brief, evidence-based tobacco cessation treatment delivered by oncology providers through the 5As (Ask, Advise, Assess, Assist Arrange) model is recommended, but provision to cancer patients remains suboptimal. Aim: Explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Sociodemographic characteristics associated with 5As receipt were gender and age. Extending our previously reported baseline findings [ 23 ], female gender was associated with lower odds of Arrange at follow-up, which is consistent with prior research demonstrating that although women are more likely to be asked about smoking, they are equally (or less) likely than men to be recommended a specific treatment or to receive follow-up tobacco treatment [ 31 33 ]. Gender differences in receipt of Arrange are concerning given evidence that women may experience greater difficulty maintaining long-term smoking abstinence than men [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Sociodemographic characteristics associated with 5As receipt were gender and age. Extending our previously reported baseline findings [ 23 ], female gender was associated with lower odds of Arrange at follow-up, which is consistent with prior research demonstrating that although women are more likely to be asked about smoking, they are equally (or less) likely than men to be recommended a specific treatment or to receive follow-up tobacco treatment [ 31 33 ]. Gender differences in receipt of Arrange are concerning given evidence that women may experience greater difficulty maintaining long-term smoking abstinence than men [ 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although baseline analyses identified clinical characteristics (diagnosis of a smoking-related cancer or comorbid smoking-related disease) as increasing a patient’s odds of reporting receipt of Ask, Advise, Assist-Medication, or Arrange [ 23 ], patients with a smoking-related cancer actually had a lower probability of being advised to quit at follow-up. This finding was unexpected in the context of our baseline analyses and previous cross-sectional research demonstrating that smoking-related cancer diagnoses typically increase the likelihood that patients receive smoking cessation counseling and assistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One factor that may contribute to this is feedback and counseling received from their physicians. We've previously shown that clinicians are more likely to advise patients on smoking cessation when they are diagnosed with a smoking‐related cancer versus a non smoking‐related cancer 31 . This may be a pathway through which patients with other smoking‐related cancers come to recognize that smoking contributed to their cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, patients with tobacco-related cancers were more likely to report being asked about their smoking and receiving advice to quit smoking from oncology clinicians when compared with patients without tobacco-related cancers. 30 However, recent studies have suggested that these discussions are not always implemented in a way that would address these feelings. 24,31 Patients with tobacco-related cancers may require proactive outreach to address depressive symptoms and stigma following a referral to programs such as TIPS.…”
Section: Jco Oncology Practice E725mentioning
confidence: 99%